Forensic audit evidence analysis with the triangle fraud theory approach - Endang Dwi Wahyuni; Driana Leniwati; Gusti Tika Luthfiana Anggriani (Universitas Muhammadiyah Malang, 2026)
Purpose: This study aims to analyze whether Vendor Masterlist, Account Payable Register, and Employee Masterlist are strong evidence in forensic audits using the fraud triangle theory approach. Methodology/approach: The method used is a quantitative survey. Data was collected through questionnaires to employees of primary consumer goods companies in Malang and Bali, and through interviews with experienced auditors, with a total of 60 valid respondents. Findings: The Supplier Master List, the Accounts Receivable List, and the Employee Master List had a significant influence on forensic audit evidence. And all three proved to be strong evidence in detecting fraud. Practical and Theoritical contribution/Originality: This study makes a practical and theoretical contribution by showing that company master data such as Supplier Master List, Business Accounts Receivable List, and Employee Master List can be used as an early detection tool for fraud. These findings enrich the forensic audit literature by linking weaknesses in internal documentation to potential fraud through a fraud triangle approach. Research Limitation: This study has limitations in the scope of the object, namely companies in the primary consumer goods sector in the Malang and Bali regions, and uses a cross-sectional data approach.